People-centred integration in a refugee primary care service: A complex adaptive systems perspective. Issue 1 (13th February 2017) - Phillips, Christine; Hall, Sally; Elmitt, Nicholas; Bookallil, Marianne; Douglas, Kirsty
Abstract : Purpose: Services for refugees and asylum seekers frequently experience gaps in delivery and access, poor coordination, and service stress. The purpose of this paper is to examine the approach to integrated care within Companion House (CH), a refugee primary care service, whose service mix includes counselling, medical care, community development, and advocacy. Like all Australian refugee and asylum seeker support services, CH operates within an uncertain policy environment, constantly adapting to funding challenges, and changing needs of patient populations. Design/methodology/approach: Interviews with staff, social network analysis, group patient interviews, and service mapping. Findings: CH has created fluid links between teams, and encouraged open dialogue with client populations. There is a high level of networking between staff, much of it informal. This is underpinned by horizontal management and staff commitment to a shared mission and an ethos of mutual respect. The clinical teams are collectively oriented towards patients but not necessarily towards each other. Research limitations/implications: Part of the service's resilience and ongoing service orientation is due to the fostering of an emergent self-organising form of integration through a complex adaptive systems approach. The outcome of this integration is characterised through the metaphors of "home" for patients, and "family" for staff. CH's model of integration has relevance for other services for marginalised populations with complex service needs. Originality/value: This study provides new evidence on the importance of both formal and informal communication, and that limited formal integration between clinical teams is no bar to integration as an outcome for patients.